2014
DOI: 10.1016/j.procbio.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic submerged fermentation by acetic acid bacteria for vinegar production: Process and biotechnological aspects

Abstract: Strictly aerobic acetic acid bacteria (AAB) have a long history of use in fermentation processes, and the conversion of ethanol to acetic acid for the production of vinegar is the most wellknown application. At the industrial scale, vinegar is mainly produced by submerged fermentation, which refers to an aerobic process in which the ethanol in beverages such as spirits, wine or cider is oxidized to acetic acid by AAB. Submerged fermentation requires robust AAB strains that are able to oxidize ethanol under sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(168 citation statements)
references
References 75 publications
3
142
0
23
Order By: Relevance
“…A comparative study of acetic acid productivity of wild-type AAB used for ethanol oxidation was reported by Gullo et al (39). Overall, mesophilic strains exhibited a significant acetic acid yield with respect to thermotolerant species (39).…”
Section: Growth Kinetics and Fermentation Of The Isolated Strainsmentioning
confidence: 93%
See 1 more Smart Citation
“…A comparative study of acetic acid productivity of wild-type AAB used for ethanol oxidation was reported by Gullo et al (39). Overall, mesophilic strains exhibited a significant acetic acid yield with respect to thermotolerant species (39).…”
Section: Growth Kinetics and Fermentation Of The Isolated Strainsmentioning
confidence: 93%
“…Overall, mesophilic strains exhibited a significant acetic acid yield with respect to thermotolerant species (39). However, thermo-adapted strains (which stably perform efficient acetous fermentation at high temperatures) were obtained after a number attempts to isolate thermotolerant mutants (39,40).…”
Section: Growth Kinetics and Fermentation Of The Isolated Strainsmentioning
confidence: 99%
“…It consists of a stainless steel equipped with aerator, charging pump, alkalograph, cooling water valve, thermostat cooling, rotameter, cooling coil, air line, air exhaust line and defoamer [11,19,29]. Aerator is the most specific part of Acetator, since this special impeller is self-aspirating, and through effective dispersion provide the highest oxygen transfer, described detail elsewhere [27].…”
Section: Submerged Methodsmentioning
confidence: 99%
“…After 96 hours above, culture growth decreased and reached the death phase because the environment no longer supported any growth (Yates & Smotzer, 2007), such as the lack of nutrients and oxygen in the medium. In submerged fermentation, consumption of oxygen is proportional to the conversion of the substrate into the product (Gullo et al, 2014).…”
Section: Profile Of Lipase Productionmentioning
confidence: 99%